دراسة تحليلية للإعجاز الاقتصادي في القرآن الكريم: آيات الميراث نموذجا - Mustafa Hasan; Mohammad Shekaib Alam (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
An inheritance or what is called in Arabic ‘Mirath’ is a process of transferring ownership from the dead to his living successors, whether the left out is money, real estate, or a legal right. The concept of Mirath and its rulings discussed in Qur'an in three verses only. However, they are very precise and considered miracle because of being all-inclusive, articulate and lucid. The research paper highlights the significance of inheritance in Islam, rationalizes why Islam has prescribed distinct share among various human entities of the same family and explores who deserve what in definite. The nature of this paper is descriptive, analytical and practical. The prime contribution of this paper is it has established the imperative role Islam has played in preserving, promoting and circulation of wealth by bringing the discussion on what is the definition of economic miracles in the Holy Qur’an, what is and what role inheritance system plays in Islam economic wise in the society and what are the rulings on inheritance in those three verses and their applications. The paper has detached all allegations that often made and cited by orientalists and liberals that Qur’an discriminates between genders and considers women inferior to men.